Impact of miR‐140 Deficiency on Non‐Alcoholic Fatty Liver Disease. Issue 13 (12th June 2018) - Wolfson, Benjamin; Lo, Pang‐Kuo; Yao, Yuan; Li, Linhao; Wang, Hongbing; Zhou, Qun
Abstract : Scope: We have previously shown that loss of miR‐140 has a pro‐fibrotic effect in the mammary gland. This study aims to investigate whether miR‐140 loss and obesity act synergistically to promote non‐alcoholic fatty liver disease (NAFLD), and to identify the underlying mechanisms. Methods and Results: Liver tissues were isolated from lean‐fat‐diet and high‐fat‐diet fed wild‐type and miR‐140 knockout mice. Using molecular staining and immunohistochemistry techniques, increased development of NAFLD and fibrotic indicators in miR‐140 knockout mice were identified. Utilizing an in vitro model system, miR‐140 was demonstrated to target TLR‐4, and miR‐140 overexpression was shown to be sufficient to inhibit palmitic acid signaling through the TLR‐4/NFκB pathway. Conclusion: These findings demonstrate that loss of miR‐140 results in increased expression of TLR‐4, sensitizing cells to palmitic acid signaling and in increased inflammatory activity through the TLR4/NFκB pathway. This signaling axis promotes NAFLD development in a high‐fat diet context and indicates the potential utility of miR‐140 rescue as a therapeutic strategy in NAFLD. Abstract : Loss of miR‐140 is sufficient to induce high hepatic inflammation in a lean‐fat diet environment, and miR‐140 deficiency works synergistically with high‐fat diet to promote development of NAFLD. This occurs in part through the lifting of miR‐140 inhibition of TLR‐4, resulting in increased TLR‐4 expression and sensitization of the cell to inflammatory palmitic acid signaling.